Saint-Rémy-de-Blot (Puy-de-Dôme) : nouvelles observations sur l’évolution architecturale de la forteresse de Château Rocher (xiiie-xxe siècle) - Mathias Dupuis (Revue Archéologique du Centre de la France)
The site of Château Rocher (Saint-Rémy-de-Blot, Puy-de-Dôme), was the object of a brief rescue excavation in the autumn of 2008, on the north-east corner of the building. Observations on the structure and the archaeological surveys carried out at the heart of this study enable a better determination of the construction history of the castle's north part. The oldest surviving architectural phase involves a building of oblong plan with rounded corners, which could date back to the end of the 12th century or the very beginning of the 13th century. This first phase gives way to an enlarged fortress confined by circular towers, which incorporate the preceding building. This second architectural campaign, later than Philippe Auguste's conquest of the Auverne, is difficult to date precisely, although certain typo-chronological clues could suggest a reconstruction during the late Middle Ages, perhaps resulting from the takeover of the castle by Jean II of Chauvigny de Blot in 1365. Finally some minor redevelopment occurs during the modern period.